Clinical performance of laminate and non‐laminate resin composite restorations: a systematic review. (December 2015) - Nguyen, KV; Sathorn, C; Wong, RH; Burrow, MF
Abstract: Background: A systematic review was undertaken to determine the clinical outcomes of resin modified glass‐ionomer cement or glass‐ionomer cement‐resin composite (RMGIC/GIC‐RC) laminate restorations and flowable resin composite (FRC)‐lined RC restorations compared to that of non‐laminate RC restorations. Methods: Electronic databases were searched and filtered for relevant papers by assessing titles, abstracts and full‐text articles. Randomized controlled clinical trials (RCTs) were included, comparing the clinical performance of RMGIC/GIC‐RC laminate restorations and FRC‐lined restorations with RC restorations as the control. The articles were categorized and critically appraised. Raw data were used for a fixed effects meta‐analysis. Results: Thirteen articles were included in the review. Five evaluated FRC‐lined restorations, and eight studies evaluated RMGIC/GIC‐RC laminate restorations, comparing with non‐laminate RC restorations. Three of eight RMGIC/GIC‐RC laminate restorations assessed only postoperative sensitivity. A meta‐analysis could only be conducted in three studies with the FRC‐lined restorations as the intervention. The meta‐analysis found no significant difference in clinical failures between FRC‐lined RC restorations and RC restorations with no lining (p > 0.05). Conclusions: Based on current clinical evidence, a FRC lining is no more advantageous than RC restorations with no FRC lining. More long‐term RCTs are required, particularly for evaluating RMGIC/GIC‐RC laminate restorations.